High-Strength Bolt Corrosion Fatigue Life Model and Application - Wang Hui-li; Qin Si-feng (The Scientific World Journal)
The corrosion fatigue performance of high-strength bolt was studied. Based on the fracture mechanics theory and the Gerberich-Chen formula, the high-strength bolt corrosion fracture crack model and the fatigue life model were established. The high-strength bolt crack depth and the fatigue life under corrosion environment were quantitatively analyzed. The factors affecting high-strength bolt corrosion fatigue life were discussed. The result showed that the high-strength bolt corrosion fracture biggest crack depth reduces along with the material yield strength and the applied stress increases. The material yield strength was the major factor. And the high-strength bolt corrosion fatigue life reduced along with the increase of material strength, the applied stress or stress amplitude. The stress amplitude influenced the most, and the material yield strength influenced the least. Low bolt strength and a low stress amplitude level could extend high-strength bolt corrosion fatigue life.